Alasan Permohonan Kasasi Penuntut Umum Dan Pertimbangan Hakim Mahkamah Agung Dalam Tindak Pidana Membujuk Anak Melakukan Persetubuhan - Dea Arsyandita; Edy Herdyanto., S.H., M.H (Sebelas Maret University, 2017)
This legal writing aims are to examine some issues, the suitability of the basic public prosecutor appeals and consideration of Supreme Court judges in criminal act persuade children copulation as stated in Article 253 and Article 256 On Criminal Procedure Code. This is normative research which prescriptive and applied research. Sources of law materials used primary law and secondary law which use of literature study on data collection techniques. Based on facts revealed at court proved that the Defendant had been copulating children as punished into Article 81 Paragraph (1) of Law Number 23 Year 2002 On Children Protection. Research concluded that The Judge judex factie in deciding the case did not apply or apply laws not as appropriate, which in terms of not considering statement of the Witnesses, statement of the Defendant as well as evidences that The Judges apply penal sanctions below minimum provisions against the Defendant. Public Prosecutor objected to penal sanctions dropped by The Judges to the Defendant because there are minimum standard rule and legal considerations of the Supreme Court which granted the public prosecutor's appeal in accordance with provisions of Article 256 on Criminal Procedure Code Keywords: Cassation, Consideration of Judge, Children Copulation